ANALISIS PEMANFAATAN SERBUK BATA RINGAN, ABU AMPAS TEBU DAN FLY ASH TERHADAP KUAT TEKAN BETON RINGAN STRUKTURAL - Bani Nur Danang; Dian Arumningsih Diah Purnamawanti; Rasyiid Lathiif Amhudo; Siti Nadia Binti Muhammad Samsuddin (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2026)
Infrastructure growth is in line with the growth of human resources, the more the population will require more infrastructure facilities. Construction infrastructure in Indonesia is currently starting to focus on development that leads to the use of structures with lightweight materials and has high resistance. This is inseparable from Indonesia's geographical location which is on the Pacific Ring of Fire which makes Indonesia prone to earthquakes. Therefore, it is necessary to conduct research on lightweight concrete that can overcome these potential hazards. This study used lightweight brick powder, bagasse ash and fly ash in replacing concrete materials. The method used is experimental by creating variations of lightweight concrete by adding lightweight brick powder amounting to 70% of the volume of fine aggregate. The results of the optimal content of bagasse ash use are 10% and fly ash 15% of the total cementitious. Testing of lightweight concrete variations was carried out on concrete aged 7, 14, 21 and 28 days. On lightweight concrete aged 28 days, a comparison was made with normal concrete. The results of the test weight of lightweight concrete aged 7, 14, 21 and 28 were 2.89 kg; 2.83 kg; respectively. 2.80 kg and 2.79 kg. The results of the lightweight concrete compressive strength test at the age of 7, 14, 21 and 28 were 16.54 MPa, 22.27 MPa, 25.25 MPa and 26.74 MPa, respectively. The resulting density ratio was 1743 kg/m3 for lightweight concrete and 2283 kg/m3 for normal concrete. The resulting compressive strength comparison from the creation of lightweight concrete at the age of 28 days from 3 test specimen samples was 26.74 MPa, 27.37 MPa and 26.10 MPa, respectively, while in 3 normal concrete samples the values were 24.19 MPa, 24.83 MPa and 26.10 MPa.